Potential ultra hard phases of ZrO2-HfO2 solid-solutions, derived from high P-T conditions - Jackson, Neil (My University, 2011)
The pressure-temperature phase diagram of this compound was explored for the rst time using angle dispersive x-ray di raction. The pressure-temperature behaviour of this solid-solution was then compared to the di raction data of the end members ZrO2 and HfO2. The investigative techniques of Raman spectroscopy and x-ray di raction were used to clarify previous Raman spectroscopy studies. The structural changes from the sevenfold coordinated monoclinic to orthorhombic-I to the ninefold orthorhombic-II (cotunnite) structure under high pressure-temperature conditions were confirmed.